Evaluation of physiological response on table tennis multiball training with different loads - Lee, Y.-L. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
Background: There are the three basic energy pathways of the human body, ATP-PC system, lactic acid system, and oxygen system. Table tennis match is mainly in the ATP-PC system. Multiball training has always been one of the major training methods of table tennis, but the intensity has not been determined. Purpose: Evaluation of physiological response on table tennis multiball training with different loads. Method: Twelve outstanding male college table tennis players (age 20.42±1.56 years, height 175.33±4.59 cm, and weight71.17±8.64 kg) were recruited in this study. Average training year was 10.33±1.26 years. Method of balance sequence is adopted to test 12 subjects which were required to accomplish 9 balls a repeated (each rep consisted of 9 balls, 1 rep interval 10 sec rest, 9-10), 18-20 and 30-33 training. 1 set consisted of 90 balls, and a total of 180 balls. The frequency was 55 balls pro minute by robot. The test type was the Falkenberg footwork. Lactate (La) level and Heart rate (HR) in baseline (R), during test (1 Set), and end of test at 1, 3, 5 min (E1, E3 and E5) were determined. Ammonia (NH3) level in R and E5. Rating of perceived exertion (RPE) in R, 1 set and E1. The three tests proceed in an interval of one week. By one-way ANOVA Repeated Measures and LSD used in the Post hoc Comparison, differences in the all dependent variables were analyzed. Results: In baseline is no difference. 30 balls-33 group exhibited higher heart rate, Ammonia and RPE in post-test immediately compared to the other tests (p<.05). The level of lactate in 9-10 group was not over 4 mmol/L lactate threshold at the beginning of test to post-test 5 min and lower than the other group tests (p<.05). Conclusions: The major finding in this study was that the multiball training of table tennis using the Falkenberg footwork test in 9 balls group was reasonable to reflect the energy utilization during competition.